Telomeres and Subtelomeres Dynamics in the Context of Early Chromosome Interactions During Meiosis and Their Implications in Plant Breeding - Aguilar, Miguel; Prieto, Pilar (Frontiers in Plant Science, 2021)
Genomic architecture facilitates chromosome recognition, pairing, and recombination. Telomeres and subtelomeres play an important role at the beginning of meiosis in specific chromosome recognition and pairing, which are critical processes that allow chromosome recombination between homologs (equivalent chromosomes in the same genome) in later stages. In plant polyploids, these terminal regions are even more important in terms of homologous chromosome recognition, due to the presence of homoeologs (equivalent chromosomes from related genomes). Although telomeres interaction seems to assist homologous pairing and consequently, the progression of meiosis, other chromosome regions, such as subtelomeres, need to be considered, because the DNA sequence of telomeres is not chromosome-specific. In addition, recombination operates at subtelomeres and, as it happens in rye and wheat, homologous recognition and pairing is more often correlated with recombining regions than with crossover-poor regions. In a plant breeding context, the knowledge of how homologous chromosomes initiate pairing at the beginning of meiosis can contribute to chromosome manipulation in hybrids or interspecific genetic crosses. Thus, recombination in interspecific chromosome associations could be promoted with the aim of transferring desirable agronomic traits from related genetic donor species into crops. In this review, we summarize the importance of telomeres and subtelomeres on chromatin dynamics during early meiosis stages and their implications in recombination in a plant breeding framework.